2021
DOI: 10.3390/biomedicines9091155
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanofibers versus Silver Nanoparticles: Time-Dependent Cytotoxicity, Proliferation, and Gene Expression

Abstract: Carbon nanofibers (CNFs) are one-dimensional nanomaterials with excellent physical and broad-spectrum antimicrobial properties characterized by a low risk of antimicrobial resistance. Silver nanoparticles (AgNPs) are antimicrobial metallic nanomaterials already used in a broad range of industrial applications. In the present study these two nanomaterials were characterized by Raman spectroscopy, transmission electron microscopy, zeta potential, and dynamic light scattering, and their biological properties were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 65 publications
(82 reference statements)
1
21
0
1
Order By: Relevance
“…In that study, multi-layer GO showed to be able to up-regulate four genes (CAT, TGFB1, FN1, and CDH1) that are relevant in biomedicine [13]. Another CBN in the form of carbon filamentous hollow materials has recently been shown to be capable of up-regulating many more genes than other types of nanomaterials, silver nanoparticles, and thus showing the great potential of CBNs in the biomedical field [14].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In that study, multi-layer GO showed to be able to up-regulate four genes (CAT, TGFB1, FN1, and CDH1) that are relevant in biomedicine [13]. Another CBN in the form of carbon filamentous hollow materials has recently been shown to be capable of up-regulating many more genes than other types of nanomaterials, silver nanoparticles, and thus showing the great potential of CBNs in the biomedical field [14].…”
Section: Introductionmentioning
confidence: 93%
“…Therefore, these results reinforce the idea of using these nanomaterials for biomedical applications such as wound healing and skin tissue engineering. Nonetheless, it is important to mention that other carbon materials such as 1D filamentous hollow carbon nanofibers showed effective results in up-regulating eight (FN1, MMP1, CAT, CDH1, COL4A1, FBN, GPX1, and TGFB1) of the thirteen analyzed genes [14].…”
Section: Gene Expressionmentioning
confidence: 99%
“…Ag can be particularly effective when applied in coatings made of nanoparticles [45] and in nanostructures [46] containing large surface-to-bulk ratio particles with considerable quantities of Ag oxide that provide a source of Ag ions to effectively kill bacteria [47]. Ag nanoparticles are used as antimicrobial agents in a broad range of industrial applications including wound dressings, food and textile area, paints, household products, catheters, implants, and cosmetics, among many others [48]. Research has shown that the size of Ag nanoparticles can significantly influence their efficacy as an antiviral agent and the effective upper size limit appears to be around 25 nm [49].…”
Section: Silvermentioning
confidence: 99%
“…Proteins spontaneously and quickly adsorb onto carbon nanoparticles, forming the so-called protein corona and covering the surface [69]. The organic components of GAM broth contain a Therefore, the results of this study show that the incorporation of a low amount (1% w/w) of filamentous 1D hydrophobic CNFs, which are longer nanoparticles and possess lower negative charge than the GO nanosheets [63][64][65][66], significantly increased the degradability of the hydrophobic PHBV after 3 months in simulated intestinal media (both acid aqueous and GAM media). The long filamentous hydrophobic CNFs incorporated into the PHBV polymer matrix creates carbon-based nanochannels through which water (in this case aqueous medium) can penetrate at ultrafast speed according to previous studies [70][71][72], increasing the total area of PHBV chains exposed to degradation.…”
Section: Degradation In Simulated Intestinal Conditionsmentioning
confidence: 79%
“…The dynamic light scattering (DLS) technique showed a particle hydrodynamic size of the GO nanosheets that ranged from 300 to 500 nm, depending on the nanofluid (polyethylene glycol, 1-octadecanothiol, or Triton X-100 surfactant) used for these measurements [65]. However, the DLS hydro-dynamic sizes of the 1D nanomaterial showed to be much larger, ranging from 811.2 to 1142 nm, depending also on the nanofluid used (DMEM or water, respectively) [66].…”
Section: Methodsmentioning
confidence: 99%